Printed diamond slot antenna with a bent microstrip line for 5.8 GHz RFID reader - Phongcharoenpanich, Chuwong; Senathong, Rewat (My University, 2012)
This paper presents the design of 5.8 GHz reader antenna for Radio Frequency Identification (RFID) system. The printed diamond slot antenna with a bent microstrip line is presented. The measured results can achieve the operating bandwidth (|S11| < -10dB) from 5.45 GHz to 6.18 GHz and can achieve the circular polarization (axial ratio < 3 dB) from 5.71 GHz to 5.89 GHz. In addition, the antenna radiates uni-directional pattern along the frequency band. © 2012 IEEE.
Keywords: Axial ratio; bent microstrip line; diamond slot; RFID; uni-directional beam